ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS DALAM MENGUKUR KINERJA KEUANGAN PADA PT. UNILEVER INDONESIA TBK TAHUN 2020 – 2022 - Lovia Nur Puspita; Adinata Kurnia Putra; Ratih Kusumastuti (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This article aims to analyze the financial performance of PT. Unilever Indonesia Tbk during the 2020-2022 period using liquidity ratios and solvency ratios. Liquidity ratios and solvency ratios are used as a tool to evaluate a company's ability to meet short-term and long-term financial obligations. This study collects financial data of PT. Unilever Indonesia Tbk from annual financial reports for the 2020-2022 period. The liquidity ratios used in this analysis include the current ratio, cash ratio, and quick ratio. Meanwhile, the solvency ratios used include the ratio of debt to equity and the ratio of long-term debt to equity